Multiple acquisitions of STIs: invitation to precision in clinical care and summons to intangibles in laboratory diagnosis - Nirmal, Kirti; Saha, Rumpa; Ramachandran, Vishnampettai G.; Battacharya, Sambit N.; Das, Shukla; Mogha, Narendra S. (Journal of Biomedical Sciences, 2017)
Background Co-existence of one sexually transmitted infection (STI) with another viral or bacterial agent may change the classical behavior of the genital infection and may provide the stimulus for reactivation. The objectives of this study were to document and appraise the relevance and importance of co-infection in STIs in their prevailing permutation and combination. Material and methods This cross-sectional study included 200 consecutive patients, attended the STI clinic of a tertiary care hospital in East Delhi with one or more complaints related to STI. Samples were collected, stained, cultured and antibody detection was done. Results A number of STIs patients had significant association with multiple co-infecting agents. Dual coinfection was seen in 53.1%, while ≥ 3 STIs pathogens were seen in18% cases. Importance of serology in detecting subclinical cases is also highlighted in the study. Conclusion Present study highlights the requirement for periodic need based surveillance of STIs for clinical intervention with challenge to clinicians for diagnosing multiple co-infections. The number of subclinical STIs in the present study underscores the importance of serology for detection of common STIs in all patients presenting to the STI clinic.